Pedagogical Worksheets: A Methodological Proposal to Teach the Spanish Language and Costa Rican Culture to Foreign Students - Morales Calderón, Álvaro (2009)
Learning a foreign language is not only limited to acquiring grammar, spelling, and good pronunciation; it goes beyond the linguistic field. This process also implies the acquisition of gestures (kinesics), behaviors, and cultural manifestations of the country where the language is spoken.